Pengaruh Gaya Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Di MAN 1 Bukittinggi - Fitria Ose; Yusti Rahmi; Nurhizrah Gistituati; Hadiyanto (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2024)
This article analyzes the impact of leadership style at Madrasah Aliyah Negeri 1 Bukittinggi. The focus is on six main leadership styles, namely transformational, transactional, autocratic, charismatic, bureaucratic and democratic. This article has provided in-depth insight into leadership styles; Democratic, transformational, bureaucratic and autocratic leadership have a positive impact on the performance of Madrasah Aliyah Negeri 1 Bukittinggi teachers. In this article, analysis of primary data and secondary data has been carried out. The analysis uses a quantitative approach, with the help of a survey instrument, based on a questionnaire survey. Secondary research has been conducted through a review of previously established literature to achieve the research objectives. The results of this article suggest that charismatic, bureaucratic and transactional leadership styles have a negative relationship with performance. Transformational, autocratic and democratic leadership styles, on the other hand, have a positive relationship with the performance of Madrasah Aliyah Negeri 1 Bukittinggi.